The Impact of COVID 19 on small businesses managed by Youths in Solwezi, Zambia - Chilekwa, John; Zambia, Kitwe; Musawa, Nsama (International Journal of Scientific Research and Management (IJSRM), 2022)
This research studies the Impact of Covid-19 on the small businesses managed by the Youths in the mining town of Solwezi in Zambia. It utilised a qualitative research design method with 50 respondents being the youth businesses in Solwezi. Data collected through survey questionnaires was the analysed using the descriptive survey design. The study found that Covid-19 had adversely affected the youth managed small businesses performance and the youth employment in Solwezi. On the other hand, this has brought the prospects of technology driven businesses solutions around Solwezi. The study recommends more investment in internet technology and remote working practices as a way of reducing the impact of pandemics in the small businesses environment. It further recommends more relief and bail out packages from the Government to be considered for small businesses with low cash reserves.